Strategi Meningkatkan Kreativitas Karyawan Di Era Industri 4.0 - Nala Tri Kusuma; Ignatius Soni Kurniawan; Dewi Sartikhah Nurjannah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The research raised in this study is the development of employees who must be able to implement the 4.0 revolution, because the transition carried out by the industry is shifting from the traditional direction to the digital era, furthermore, to survive in competition, companies or organizations must be able to manage employees creatively who are able to improve their performance. performance. This research aims to test the mediation of intrinsic motivation between psychological empowerment toward creativity employee. The population used is private employees in Yogyakarta. The data taken using a questionnaire were analyzed using multiple linear regression and Baron Kenny. The results showed that there was a positive effect of psychological empowerment on intrinsic motivation with a t value of 8,518 and a significance 0.01. There is a positive influence from psychological empowerment and intrinsic motivation partially on creativity employee. Intrinsic motivation is also able to mediate the psychological empowerment relationship to creativity employee